The Role of the Body in Instrumental and Vocal Music Pedagogy: A Dynamical Systems Theory Perspective on the Music Teacher's Bodily Engagement in Teaching and Learning - Bremmer, Melissa; Nijs, Luc (Frontiers in Education, 2020)
Instrumental and vocal teachers often employ their body in teaching to facilitate sensorimotor engagement with the voice or an instrument. Yet, teacher's bodily engagement in instrumental and vocal education is scarcely addressed in music educational research studies. In our view, this scarcity is related to the lack of a framework about the role of the music teacher's body in instrumental and vocal education. In this article, we will adopt a dynamical systems theory perspective to set first steps in conceptualizing the role of the instrumental and vocal teacher's body in teaching and learning music. From this perspective, learning processes are viewed as emerging from the learner's goal-oriented, situated, adaptive actions in the learning environment. Teachers play a significant role in that environment, due to the different types of constraints (e.g., environmental and task constraints) they can introduce to aid learners in finding a solution for a musical task. In this article, we argue that different types of teacher's bodily engagement can act as constraints in instrumental and vocal music learning, thereby facilitating the learning process in non-verbal ways. To demonstrate this, we describe four types of bodily involvement: physical modeling, action demonstration, pedagogical gestures and touch. In summary, based on existing theoretical and empirical research, the article will present a first conceptualization of the role of the music teacher in instrumental and vocal education viewed from a dynamical systems approach.